Subjective image quality of digitally filtered radiographs acquired by the Durr Vistascan system compared with conventional radiographs - ERÇALIK YALÇINKAYA, ŞEBNEM (MOSBY-ELSEVIER, 2006)
Objectives. To compare the different digital filters implemented in the Durr Vistascan system with conventional film and to analyze the filter specificity to anatomic structures. Study design. Ten panoramic image pairs and 10 periapical image pairs 0 digital and I conventional) were obtained from 20 patients conventionally and digitally. The display quality of different anatomic image structures was rated subjectively on a 5-point scale. The responses were evaluated using ANOVA and Tukey-Kramer post hoc tests. The intraobserver reliability was evaluated by Cohen's kappa statistics. Results. The display quality of anatomic structures was rated higher by using Caries I or 2 filters for periapical and Periodontal I or 2 filters for panoramic images, whereas nonfiltered and Noise Reduction-filtered images received the lowest scorings compared to all other digital image modalities (P < .0097). The superiority of conventional radiographs to the digital ones was statistically significant (P < .0039 and P < .0152 respectively). Conclusions. Depending on the diagnostic task, digital images of the Vistascan system should be filtered before examination. Perfect conventional radiographs still remain the gold standard for image quality.
Keywords: TO-NOISE RATIO; PHOSPHOR SYSTEMS; CARIES; ENHANCEMENT; STATE; FILM